Effects of fluorination on the electrochromic performance of benzothiadiazole-based donor–acceptor copolymers1. Issue 21 (7th June 2015) - Neo, Wei Teng; Ong, Kok Haw; Lin, Ting Ting; Chua, Soo-Jin; Xu, Jianwei
<x xml:space="preserve">Abstract</x> Fluorination of electron acceptors in donor–acceptor type conjugated polymers leads to a substantial enhancement in the long-term redox stability of electrochromic devices.